KEPENTINGAN ISRAEL DALAM MENORMALISASI HUBUNGAN DIPLOMATIK ISRAEL-SUDAN - Wicaksana, Abu Dzar Al Ghiffari; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study analyzes "Israel's Interests in Normalizing Diplomatic Relations between Israel and Sudan" with the aim of finding out what Israel's interests are in conducting diplomatic relations with Sudan, also known as normalization. Normalization is a program initiated by Israel in its efforts to approach neighboring countries, especially in the Arab region. As a country that is quite close to Israel, Sudan is one of Israel's targets in expanding its normalization program. Although Sudan is a country that is below average, it turns out that Israel has interests there. So far, the normalization program initiated by Israel with Sudan has been carried out to support diplomatic relations between the two and as an instrument in establishing good relations with other countries in the region in achieving its national interests. This study uses qualitative and descriptive methods, referring to the neorealist perspective and the concept of national interest. This study found that Israel uses normalization as their diplomatic strategy to approach other countries, including achieving its national interests in the political, economic, military, and cultural fields. The results of this study prove that through normalization, Israel has succeeded in approaching neighboring countries and also countries that want to join by making offers to these countries. Keyword: Normalization, National Interest, Neorealism